Hemodialysis Culture of Serratia marcescens in a Goat-Artificial Kidney-Fermentor System - Quarles, John M. (1974)
Hemodialysis was employed to simulate in vivo conditions for growth in mammalian blood, but without phagocytosis, by using the goat and Serratia marcescens as a host-parasite model. The blood stream was shunted surgically via prosthetic tubing from a carotid artery through the hollow-fiber membranes in an artificial kidney hemodialyzer and back into a jugular vein. The dialysate solution concurrently was pumped from a modular fermentor through the hemodialyzer jacket outside of the membranes and back into the fermentor. Hemodialysis between the two circuits was maintained continuously. When equilibrium was attained, bacteria inoculated into the dialysate circuit multiplied first exponentially at the maximal rate and then arithmetically at a lesser rate equally well under aerobic or anaerobic conditions. When a population of about 10(9) viable bacteria/ml was exceeded, the goat reacted acutely with signs of general toxemia, pyrexia, and leukopenia, apparently because of dialyzable toxic material produced by the culture. The maximal molecular size of the toxic material was defined relative to a rigid globular protein of 15,000 in molecular weight and 1.9 nm in hydrodynamic radius or to a flexible fibrous polyglycol of 5,500 in molecular weight and 2.6 nm in hydrodynamic radius, based on determinations of the membrane porosity threshold for dialysis.